Cognitive Reserve and the course of Alzheimer´s disease - Sobral, M.; Pestana, M.H.; Paúl, C. (28th International Congress of Applied Psychology, 10 july 2014, Paris, 2014)
Cognitive reserve (CR) is a hypothetical construct that has been used to inform of cognitive aging and describes the capacity of the adult brain to tolerate the effects of the neurodegenerative process.